2021
DOI: 10.1021/acsomega.1c03154
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced H2 Storage Capacity of Bilayer Hexagonal Boron Nitride (h-BN) Incorporating van der Waals Interaction under an Applied External Electric Field

Abstract: Lightweight two-dimensional materials are being studied for hydrogen storage applications due to their large surface area. The characteristics of hydrogen adsorption on the h-BN bilayer under the applied electric field were investigated. The overall storage capacity of the bilayer is 6.7 wt % from our theoretical calculation with E ads of 0.223 eV/H 2 . The desorption temperature to remove the adsorbed H 2 molecules from the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…On investigating the optimized structure upon single hydrogen insertion, interlayer distance expands from 3.47 → 4.34 Å. Such expansion in interlayer distance upon hydrogen molecule adsorption inside the cavity was also observed in bilayer boron nitride. ,, …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…On investigating the optimized structure upon single hydrogen insertion, interlayer distance expands from 3.47 → 4.34 Å. Such expansion in interlayer distance upon hydrogen molecule adsorption inside the cavity was also observed in bilayer boron nitride. ,, …”
Section: Resultsmentioning
confidence: 72%
“…The preferred hexagonal site has also been verified from the available literature on the monolayer and bilayer hexagonal boron nitride systems. 34,91,94 The average adsorption energy [E ads (eV/H 2 )] are computed using the following equation:…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…The theoretically calculated overall storage capacity of the bilayer is 6.7 wt % with Eads of 0.223 eV/H2. 112 TiO2-coated boron nitride nanofibers showed improved morphology, surface area and hydrogen storage. 113 In a recent study, alkali-earth metal (Be, Mg and Ca) encapsulated Al12N12 nanoclusters have been considered for hydrogen storage via adsorption and demonstrated: an increase in adsorption energy when compared to untreated Al12N12 and H2-Al12N12 and a decrease in the HOMO-LUMO energy gap.…”
Section: Small Inorganic/organic Moleculesmentioning
confidence: 99%
“…Theoretical studies of hydrogen adsorption on the pristine bilayer hexagonal boron nitride (h-BN) show a trend of decreasing binding energies and desorption temperatures that is useful for potential H 2 storage. The calculated overall storage capacity of the h-BN is 6.7 wt % with E ads of 0.223 eV/H 2 . Studies of heat treatment effects on TiO 2 -coated boron nitride nanofibers revealed that the highest hydrogen adsorption occurred at room temperature …”
Section: Hydrogen Productionmentioning
confidence: 99%
“…The calculated overall storage capacity of the h-BN is 6.7 wt % with E ads of 0.223 eV/H 2 . 123 Studies of heat treatment effects on TiO 2 -coated boron nitride nanofibers revealed that the highest hydrogen adsorption occurred at room temperature. 124 Recently, aluminum nitride nanoclusters have been investigated for hydrogen storage.…”
Section: ■ Hydrogen Productionmentioning
confidence: 99%